The SAGE handbook of social geographies - Smith, Susan 1956-. (Los Angeles London SAGE, 2010)
Social geography has been concerned with the ways in which social relations, social identities and social inequalities are produced, their spatial variation, and the role of space in constructing them. This title is divided into five sections which develop these fundamental concerns.
Includes bibliographical references and index.
Keywords: Human geography; Electronic books